Systemic lupus erythematosus in childhood. Issue 4 (August 1981) - Caeiro, F; Michielson, F M; Bernstein, R; Hughes, G R; Ansell, B M
Abstract : The clinical and serological features have been analysed retrospectively in 42 patients with an onset of systemic lupus erythematosus (SLE) up to 16 years of age. Thirty-seven (88.1%) were female and 5 (11.9%) male. The mean age of onset was 12.3 years (range 7-16); 11 patients were 10 years or under. The mean duration of disease from diagnosis was 7.1 years (range 6 months-25 years). There were 6 deaths, 3 from infection, 2 from renal failure, and 1 from heart failure. Survival was calculated both from the date of onset and from the date of diagnosis. With the latter the estimated overall survival at 5 years was 82.6% and at 10 years 76.1%. The survival for patients with lupus nephritis was 59.5% at 5 years and 47.6% at 10 years. These data suggests that SLE in childhood is not necessarily associated with a poor prognosis, though renal involvement is still serious. There appeared to be no major differences between prepubertal, adolescent, and adult SLE with respect to clinical and serological findings.